I-06 Long interspersed nuclear element-1 retroelements are expressed in patients with systemic lupus erythematosus and primary SJOGREN'S syndrome and induce type I interferon. (31st August 2016) - Mavragani, Clio P; Sagalovskiy, Irina; Guo, Qiu; Nezos, Adrianos; Kapsogeorgou, Efstathia K; Lu, Pin; Zhou, Jun Liang; Kirou, Kyriakos A; Seshan, Surya V; Moutsopoulos, Haralampos M; Crow, Mary K
Abstract : Background: Recent studies have documented numerous common and several rare genetic variants that are associated with SLE, but the endogenous and exogenous triggers that initiate and perpetuate disease have not yet been defined. The presence of elevated serum type I interferon (IFN-I) activity and a broad signature of IFN-I-induced gene transcripts and proteins in blood and tissue of patients with lupus and other systemic autoimmune diseases, including primary Sjogren's syndrome (SS), are consistent with a viral trigger, but available data have not identified an exogenous virus as an etiologic agent in these diseases. To identify disease-relevant triggers of the IFN-I pathway we investigated whether endogenous virus-like genomic repeat elements, normally silent, might be expressed in patients with systemic autoimmune disease, activate an innate immune response and induce IFN-I. Materials and methods: Expression of IFN-I and long interspersed nuclear element-1 (LINE-1; L1) was studied in kidney tissue from lupus patients and minor salivary gland (MSG) tissue from patients with primary SS by PCR, western blot and immunohistochemistry. Induction of IFN-I by L1 was investigated by transfection of plasmacytoid dendritic cells (pDCs) or monocytes with an L1-encoding plasmid or L1 RNA. Involvement of innate immune pathways and altered L1 methylation were assessed. Results: L1 mRNA transcripts were increased in lupus nephritis kidneys and in MSG from SS patients and correlated with IFN-I expression. Using bisulfite-PCR pyrosequencing, a negative correlation of L1 expression with% L1 methylation was documented for the majority of L1 promoter CpG sites tested, suggesting that augmented demethylation processes, or alternatively impaired remethylation, might account for the observed L1 overexpression in SS MSG tissues. L1 open reading frame 1/p40 protein and IFN-beta were expressed in MSG ductal epithelial cells and in lupus kidneys, and IFN-alpha was detected in infiltrating pDCs. Transfection of pDCs or monocytes with L1-encoding DNA or RNA or U1 RNA, but not hY3 RNA, induced IFN-I. Inhibition of TLR7/8 reduced L1 induction of IFN-alpha in pDCs, and an inhibitor of IKK-epsilon/TBK1 abrogated induction of IFN-I by L1 RNA in monocytes. Conclusions: L1 genomic repeat elements represent endogenous nucleic acid triggers of the IFN-I pathway in SLE and SS and may contribute to initiation or amplification of autoimmune disease. Investigation of the genetic and environmental factors that alter regulation of L1 elements and increase availability of these endogenous immunostimulatory factors should suggest novel therapeutic interventions in SLE and related diseases. Acknowledgements: We acknowledge Evi Poulou and Effie Papageorgiou for assistance in immunohistochemical and Western Blot stainings.